Social work with disabled people - Oliver, Michael, 1945- 4 0 16; Sapey, Bob.; 5 (Basingstoke, Hampshire ;;New York : Palgrave Macmillan, 2006)
This classic text has been essential reading for students and professionals in the field of social work and disability for twenty years. Extensively revised and updated, the third edition examines the ways in which disabled people have increasingly been able to manage and develop their own services. It reconstructs social work practice in the light of these and the latest policy changes, stressing throughout the importance to practice of thinking critically about the welfare response to disability. -- Provided by publisher.
Includes bibliographical references (p. 193-210) and index.
Keywords: 2 -- 0; 6; Practice -- Social work with people with disabilities;Social service -- Great Britain.;Great Britain. -- 20; 20; 2